Invasion of the Carribean by the hibiscus mealybug, Maconellicoccus hirsutus Green [Homoptera : Pseudococcidae] - Sagarra, L.A.; Peterkin, D.D. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1999)
Since its accidental introduction into the island of Grenada in 1994, Maconellicoccus hirsutus [Homoptera : Pseudococcidae], commonly named the Hibiscus or Pink Mealybug (HMB), has been inexorably spreading through the Caribbean islands where it has become a major pest on several crops in 24 Caribbean Islands. This pest was also reported in Guyana threatening South and Central America. M. hirsutus is a very prolific pest that injects a toxin at the point of feeding, causing severe distortion of leaves, new shoots and fruit. Initial use of physical and chemical control methods were ineffective. In addition, because of its wide host range and its rapid geographie expansion, not only to agricultural land but also to home gardens and forest areas, biological control appeared as the most suitable method to manage the HMB populations. Three natural enemies were selected for this biocontrol effort: the predatory beetles Cryptolaemus montrouzieri Mulsant and Scymnuscoccivora Ramkrisna [Coleoptera : Coccinellidae] and the parasitoid Anagyruskamali Moursi [Hymenoptera : Encyrtidae]. A. kamali and C. montrouzieri were highly effective in bringing HMB populations under control. In newly infested countries, early introduction of biological control agents resulted in effective management of the pest. This experience provided a model for future management of other alien invasive pest species in the region.